Pro-environmental actions undertaken in France during operation of motorways - Bugajska, Agnieszka; Kulig, Andrzej (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
Road investments, including motorways and expressways, are among the projects which can have a significant impact on the environment. For this reason the proper evaluation of this impact is required, as well as its effective elimination, mitigation or compensation. The impact of the project on the environment can be observed already during the construction stage, and then sometimes on an even larger scale during the operation stage of the road infrastructure. Therefore, a proper ex‑post evaluation of the real impact of such projects is a very important and indispensable part of the process of environmental impact assessment (EIA). It enables taking corrective actions or ensuring effective operation of environmental protection equipment. Road operators can also take many other pro-environmental actions to reduce the impact of these investments on the environment. Thanks to its extensive road network and long-established legal requirements and official methodical guidance, France has an important experience in the field of realization of mandatory environmental ex‑post evaluation reports, as well as in implementing multiple other projects regarding the protection of the environment that do not arise from legal obligations. The paper presents examples of good practices and pro-environmental actions undertaken during the operation stage of certain motorways in France. These actions contribute to better integration of the motorways with the surrounding area and often combine environmental and socio-economic aspects supporting the principle of sustainable development.